Understanding and responding to economic abuse - Sharp-Jeffs, Nicola (Emerald Publishing Limited, 2022)
Despite being recognised by victim-survivors as a tactic used by abusers, economic abuse has received little attention in research, policy, or practice. Written by an internationally recognised expert on economic abuse, this powerful book provides a crucial validation of the lived experience of victim-survivors, and highlights the urgent need to develop effective responses to the issue. Breaking fresh ground, Understanding and Responding to Economic Abuse exposes the many ways in which abusers seek to control their intimate partners through economic resources and reinforces the importance of holding abusers accountable for their behaviour. Whilst the focus of this book is on Westminster policy in the UK, the author highlights how the case for 'naming' and defining economic abuse in statute has wider resonance. Making a trailblazing case for recognising this form of abuse, Sharp-Jeffs argues the case to expand the coordinated community response model to domestic abuse to address economic control through involving 'non-traditional' stakeholders such as money/debt advice organisations and the financial services sector, alongside specialist domestic abuse services and statutory agencies. Coming in the wake of the Domestic Abuse Act (2021), which broadened discourse from financial to economic abuse, Sharp-Jeffs turns our attention to this critical momentum for change and makes an important step towards shining a light on a form of coercive and controlling behaviour which has been invisible for too long.
Keywords: Family violence.; Family & Relationships, Abuse -- General.; Domestic violence.; elektronické knihy; electronic books